Significados e sentidos sobre parto e nascimento dos participantes de uma exposição interativa - Ana Luiza Nunes Abreu (2019)
The Brazilian obstetric context, in which high rates of caesarean, prematurity and obstetric violence prevail, reveals complex cultural constructions on the theme, involving ethical, economic, political and sociohistorical aspects. Aiming at transforming the population‟s perceptions and behaviors related to childbirth and birth, the Exhibition Senses of Birth (SoB) was developed with innovative and multidisciplinary methodology. A rich research scenario is revealed, with relevance to the theme, for highlighting gestating, giving birth and breastfeeding experiences for all people, not only women or health professionals. In an itinerant and free manner, through sensorial experience and information based on updated scientific evidences, the Exhibition proposes, in addition to cultural intervention, social mobilization, education and research. This study is part of one of the research fronts of the project linked to the Exhibition. With a qualitative approach, the objective was to understand the significances and meanings of childbirth and birth to the SoB participants. The Sociohistorical Psychology was used as theoretical reference, developed from Vygotsky, based on dialectical materialism. To do so, the material of four Focus Groups (FG), comprised in total of 29 Exhibition participants, was analyzed. The FG were carried out after the participants‟ visit to SoB, between April and June of 2015, during the setups in Belo Horizonte. Data was organized and analyzed from the proposal of the Nuclei of Meanings, by Aguiar and Ozella (2006), inserted in the mentioned theoretical approach. The results indicated three main cores emerged after the data interpretation process: a) How to make what I think about childbirth and birth a subject matter – resignification of being born/giving birth experiences through generations and changes in the way of looking at childbirth and birth from other counter-hegemonic narratives; b) the challenge of listening to women – significances and meanings about normal birth and caesarian from the perspective of women and the knowledge and affections acquired/felt during the Exhibition; c) the baby‟s voice – rethinking the adultcentric perspective and understanding the baby as an active subject at birth. Transgenerationality, autonomy and protagonism, gender and biopower are concepts that dialogue with the data found, revealing the dialectical movements that permeate the constructions of significances and meanings about childbirth and birth. It is considered that the perspective of transforming obstetric reality can happen exactly in the dialogue between the everyday of human relations, the history and the reflection spaces, like the Exposition Senses of Birth.